Cardiac pathophysiology: exploring online education trends among iranian students. - Ayatollahi, Ali; Mohammadpour, Mojtaba; Naghdi, Taghi; Rad, Zahra Kamary; Abdi, Saeid (Revista Latinoamericana de Hipertensión, 2023)
Undoubtedly, online education has emerged as a prominent and effective approach, particularly in the context of the Covid-19 pandemic, for students. On one hand, this method has evolved significantly owing to the rapid advancements in communication technologies. On the other hand, it has become indispensable due to the Covid-19 pandemic and the necessity to suspend traditional in-person education. It has proven to be one of the most impactful methodologies within the realm of academic education. In this study, we aim to delve into the field of cardiac pathophysiology, exploring the intricate workings of the heart and its physiological processes. Cardiac pathophysiology is a branch of medicine that delves into the deviations from normal heart function and structure, seeking to comprehend the underlying mechanisms of various cardiac disorders. This descriptive-analytic research focuses on a cohort of 112 undergraduate, postgraduate, and PhD students in Iran. A meticulously crafted questionnaire was employed to assess their experiences and perceptions of online courses and their educational objectives. We conducted a comprehensive analysis of student demographics based on various criteria, and the outcomes of online education were compared across different educational levels. Statistical analysis was performed using SPSS software to derive meaningful insights. The study findings revealed that a majority of students across all three academic levels expressed satisfaction with over 60% of their online courses. Interestingly, as the academic level increased, student satisfaction also demonstrated an upward trend. Notably, 50.9% of the participants indicated a desire to continue with online classes even after the conclusion of the Covid-19 pandemic. This underscores the effectiveness and acceptance of online education. However, it is essential to acknowledge that online education is not without its challenges. Issues such as slow internet connections and limited interactions with instructors can be perceived as drawbacks of this method. Despite these challenges, the overall consensus among students suggests that online education has been a valuable and satisfactory mode of learning for them.